Western Union Telegram from Blair Clark to Jane Tolmach - Blair Clark:::::: (1968)
A Western Union telegram that invites Jane Tolmach to a California McCarthy for President Committee reception on August 10 at the Sky Room of the El Mirador Hotel. The event offers an opportunity to meet Senator Eugene McCarthy, with arrangements available for a private meeting upon request. The telegram provides contact information for Mike Novelli to RSVP and is signed by Blair Clark, National Campaign Manager.